The transformation of civil society : an oral history of Ukrainian peasant culture, 1920s to 1930s - Noll, William (2023)
"The book is oral history, based on extensive interviews in the early to mid-nineties with elderly villagers throughout Ukraine. The book has two goals: first, to describe the catastrophic terror unleashed by Soviet power on the countryside in the early 1930s, beginning with wholesale deportations and evictions, followed by the process of collectivization in Ukraine. Noll shows the relationship between these events and the great famine of 1932-33 by framing the Holodomor within the context of what immediately preceded it and what immediately followed. He describes this through the eyes of the peasant participants themselves. The second aim is to illustrate the connection between the terror, the wholesale evictions, and collectivization followed by famine, and the Soviet state's near destruction of traditional peasant culture and ritual as they had existed before collectivization and the famine. The primary sources used throughout are oral histories of those who witnessed the terror and/or who participated in the terror: more than four hundred villagers in Ukraine who lived through the debacle as young adults or teenagers and who were interviewed in 1993-95 (the final decade of life for many of this generation). Noll does not attempt to present a meticulous historical overview of the time. Instead, he provides a sampling of the points of view of villagers on the near total destruction of their world as they knew it